P-cadherin induces anoikis-resistance of matrix-detached breast cancer cells by promoting pentose phosphate pathway and decreasing oxidative stress - Sousa, Bárbara (2020)
Successful metastatic spreading relies on cancer cells with stem-like properties, glycolytic metabolism and increased antioxidant protection, allowing them to escape anoikis and to survive in circulation. The expression of P-cadherin, a poor prognostic factor in breast cancer, is associated with hypoxic, glycolytic and acidosis biomarkers. In agreement, P-cadherin-enriched breast cancer cell populations presents a glycolytic and an acid-resistance phenotype. Our aim was to evaluate whether P-cadherin expression controls the glycolytic and oxidative phosphorylation fluxes of matrix-detached breast cancer cells, acting as an antioxidant and enhancing their survival in anchorage-independent conditions. By using matrix-detached breast cancer cells, we concluded that P-cadherin increases glucose-6-phosphate dehydrogenase expression, up-regulating the carbon flux through the pentose phosphate pathway, while inhibiting pyruvate oxidation to acetyl-coA via pyruvate dehydrogenase kinase-4 (PDK-4) activation. Accordingly, P-cadherin expression conferred increased sensitivity to dichloroacetate (DCA), a PDK inhibitor. P-cadherin expression also regulates oxidative stress in matrix-detached breast cancer cells, through the control of antioxidant systems, such as catalase and superoxide dismutases (SOD)1 and 2, providing these cells with an increased resistance to doxorubicin-induced anoikis. Importantly, this association was validated in primary invasive breast carcinomas, where an enrichment of SOD2 was found in P-cadherin-overexpressing breast carcinomas. In conclusion, we propose that P-cadherin up-regulates carbon flux through the pentose phosphate pathway and decreases oxidative stress in matrix-detached breast cancer cells. These metabolic remodeling and antioxidant roles of P-cadherin can promote the survival of breast cancer cells in circulation and in metastatic sites, being a possible player in breast cancer therapeutic resistance to pro-oxidant-based interventions.